Esg Performance And Firm Performance In Indonesia: Does External Assurance Matter? - Lalu Rahmat Sohdi; Armadani Armadani, Komang Adhitanaya, Al Putri Oktavia (YUME : Journal of Management, 2026)
The high level of stakeholder awareness of sustainability issues creates a demand for companies to practice in accordance with principles that prioritize sustainability. This study aims to examine the moderating role of external assurance on the relationship between ESG performance and firm performance. This study uses a panel data regression approach to test the research hypothesis. The sample for this study consists of non-financial companies and includes 1,535 total observations. This study's findings reveal that ESG performance positively affects firm performance. However, the enhancement of ESG performance is not significantly moderated by external assurance. To the author's knowledge, this study is the first of its kind in Indonesia. Therefore, this study significantly fills the gap in previous research by comprehensively analyzing and providing empirical evidence regarding the role of ESG in improving firm performance.